Fodor's in focus Acapulco - Bluestone, Carissa; Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to Acapulco, with maps and information on accommodations and restaurants, shopping and entertainment, and other interesting places to see.
"Portions of this book appear in Fodor's Mexico.".
Includes index.
Adult
Keywords: Acapulco (Mexico) -- Guidebooks; Acapulco (Mexico) -- Guidebooks